A territorialização da produção de fumo na mesorregião oeste do Paraná: sujeição da renda da terra e as formas de resistência do campesinato - Vicini, Jennifer Paola (2019)
The present research seeks to analyze and understand the contradictions involved in the production of tobacco in the western mesoregion of Paraná, especially with the focus on 6 municipalities, which have the highest production: São Miguel do Iguaçu, Itaipulândia, Missal, Santa Helena, Mercedes and Marechal Cândido Rondon. In this spatial clipping, one questions the understanding about a set of contradictions that touches peasant agriculture and capital. It seeks to investigate how capitalism appropriates non-capitalist relations of production for the accumulation, the capitalist monopolization of peasant territory by the system of integration and the strategies of existence and resistance that the peasants develop before the subordination and subjection of the income of the land to which are subject to this relationship of tobacco production, as well as the economic and moral effects of the tobacco production chain. In this sense, a discussion is also made for the theoretical understanding of the peasant concept, in order to emphasize and justify the importance of its use, as well as to contextualize the existing contradictions regarding the expansion of capitalism in the countryside from the term, agribusiness and family farming. Therefore, it is important to understand the contradictions that exist in the production of tobacco, especially the reasons why it occurs on small property. In this context, it is still important to cover how land concentration in the field is increasingly happening, as well as through this research to unveil the intrinsic links to the integration of agriculture and industry in the small properties for tobacco cultivation, given that there are several contradictions that revolve around capitalism, primarily, when it enters the countryside and excludes the peasantry, or subordinates it to ensure its expanded reproduction. Thus, the objective was to understand the territorialization of tobacco production in this region, as well as to understand the context that leads peasants to adhere to tobacco cultivation and the contradictory developments in this process.